Operasi pelengkapan telaga - Ismail, Issham (Penerbit UTM, 2003)
This textbook/reference book was written in Malay. It covers the preparation for well completion operation, planning of subsurface tools installation depth in a tubing string, well completion operation, wireline operation, and preparation of well completion report.